Exercise in myositis: What is important, the prescription or the person?. Issue 2 (June 2022) - Ramdharry, Gita M.; Anderson, Martin
Abstract: Our aim for this narrative review was to undertake a search of studies into exercise for people living with Idiopathic Inflammatory myopathies (IIM). We explored the strength of existing evidence with a particular consideration for the implications for people living with IIM and what is important to them. The search strategy from the 2021 Cochrane Physical Activity review in neuromuscular disease was used, and we selected articles that included people with IIM, including Dermatomyositis (DM), Inclusion Body Myositis (IBM), Immune Mediated Necrotising Myopathy (IMNM) [also known as necrotizing autoimmune myopathy (NAM)], and Polymyositis (PM). 2967 records were screened and 16 were included in this review. Safety of exercise was demonstrated in nine articles, using a range of measures of disease activity, serum creatine kinase, indicators of inflammation, pain, or fatigue. Two studies that took muscle biopsies showed no evidence of increased inflammation. Aerobic exercise protocols were used in 8 studies across conditions and demonstrated improvements in cardiorespiratory fitness or exercise capacity. Six studies of strength training observed improvements in muscle function, with two studies reporting muscle biopsy results of amplified immune response and up regulation of genes related to recycling of damaged proteins. Nine of 13 studies that measures functional outcomes showed significant improvements, and evidence for behaviour change was observed in a study of a self-management intervention. The evidence of safety and effect of training is reassuring and welcome, and we now need to explore how we support people to incorporate exercise and physical activity longer term into active lifestyles.